THE EFFECT OF NUTRITION COUNSELING ON THE PROSPECTIVE BRIDES KNOWLEDGE IN THE ANEMIA PREVENTION AT UPTD PUSKESMAS WONOGIRI 1 - Endah Wilarsih; Anik Kurniawati; Suroso Suroso (Universitas Pahlawan Tuanku Tambusai, 2022)
Prospective brides who suffer from anemia are at risk of developing anemia during pregnancy. This will have a negative impact on the growth and development of the fetus in the womb and have the potential to cause complications in the pregnancy and childbirth. Anemia can increase the risk of miscarriage, stunted fetal growth, premature birth, low birth weight, and bleeding that can cause death. Therefore, the importance of the knowledge and awareness of prospective brides about the importance of pre-conception nutrition is something that cannot be ignored. The objective of this research was to determine the effect of nutritional counseling on the prospective brides’ knowledge in preventing anemia at UPTD Puskesmas Wonogiri 1. This type of research was a quasi-experimental with a one group pretest-posttest design. The sampling technique was total sampling, the number of samples was 25 prospective brides who had their premarital health checked at the UPTD Puskesmas Wonogiri 1. The data analysis technique used the Wilcoxon signed rank test. The results of this study showed that the average value of the respondents’ knowledge before being given nutritional counseling was 56.40 and after being given nutritional counseling was 75.60. There was an increase in the average knowledge of 19.20. The results of the analysis with the Wilcoxon signed rank test statistical test obtained a p-value of 0.000 (p <0.05). There was an effect of nutritional counseling on the prospective brides’ knowledge in preventing anemia at the UPTD Puskesmas Wonogiri 1. Keywords: Nutrition counseling, prospective brides’ knowledge, anemia prevention